AN OVERVIEW OF THE OPPORTUNITIES OFFERED BY THE ADVANCEMENT OF INFORMATION AND COMMUNICATION TECHNOLOGY IN THE FIELD OF PHYSICAL EDUCATION AND SPORTS - Radu-Tiberiu ȘERBAN; Alin Marius BACIU (Cluj University Press, 2022)
Introduction. With the outbreak of the COVID-19 pandemic, caused by the novel coronavirus, major challenges have arisen in terms of the development of the teaching process and sports training. For some of them, the solution was offered by the already existing hardware and software technologies, and this created new educational contexts, as well as opportunities for adaptation and evolution of the teaching and training process. Objectives. Identify in the literature some principles, guidelines, and recommendations regarding the implementation of technology in the educational and training process. Methods. In this paper, the method of studying the literature was used, using information published in international databases. Results. The specialized literature offers many studies on the subject of education assisted by information and communication technology tools, being available examples of success in the specialized practice. Conclusions. The challenges and objectives of current education must be considered in the incorporation of technology into education before deciding how information and communication technology tools can be used to achieve them. The educational context has adapted to the current times, teachers become guides and designers of learning situations where technology is a tool that must be used masterfully by them. Received 2022 May 16; Revised 2022 June 14; Accepted 2022 June 28; Available online 2022 June 30; Available print 2022 August 30. REZUMAT. O privire de ansamblu asupra oportunităților oferite de avansul tehnologiei informației și comunicațiilor în domeniul educației fizice și sportului. Introducere. Odată cu izbucnirea pandemiei de COVID-19, cauzată de noul coronavirus, au apărut provocări majore în privința desfășurării procesului didactic și a antrenamentelor sportive. Pentru o parte dintre acestea, soluția a fost oferită de tehnologiile hardware și software existente deja, iar acest lucru a creat noi contexte educaționale, precum și oportunități de adaptare și evoluție a procesului didactic și de antrenament. Obiective. Identificarea în literatura de specialitate a unor principii, direcții și recomandări în privința implementării tehnologiei în procesul educațional și de antrenament. Metode. În realizarea acestei lucrări s-a folosit metoda studiului literaturii de specialitate, folosind informații publicate în bazele de date internaționale. Rezultate. Literatura de specialitate oferă o cantitate mare de studii pe tema educației asistate de instrumentele tehnologiei informației și a comunicațiilor, fiind disponibile exemple de succes din practica de specialitate. Concluzii. În încorporarea tehnologiei în educație trebuie avute în vedere provocările și obiectivele educației curente înainte de a decide cum pot fi utilizate instrumentele din tehnologia informației și a comunicării la atingerea acestora. Contextul educațional s-a adaptat vremurilor actuale, profesorii devin ghizi și designeri ai situațiilor de învățare unde tehnologia este o unealtă care trebuie folosită cu măiestrie de către aceștia. Cuvinte cheie: educație fizică, sport, tehnologia informației.